HIV prevalence and risk factors in infants born to HIV positive mothers, measured by dried blood spot real-time PCR assay in Tigray, Northern Ethiopia - Mulu Lemlem Desta; Muthupandian Saravanan; Haftamu Hilekiros; Atsebaha Gebrekidan Kahsay; Nesredin Futwi Mohamed; Alefech Addisu Gezahegn; Bruno S. Lopes (BMC, 2019)
Abstract Background Infants infected during pregnancy or while breastfeeding requires early HIV diagnosis at 6 weeks after birth to identify HIV infection and timely treatment. The objective of this work was to determine the prevalence and associated risk factors of HIV among HIV exposed infants in the Tigray regional state, Northern Ethiopia. Methods A cross-sectional study was conducted on 350 exposed infants born to HIV seropositive mothers from September 01 to December 30, 2016. Convenient consecutive sampling technique was employed to enroll HIV exposed infants from age 6 weeks to 18 months attending prevention of mother to child transmission (PMCT) clinic at Anti Retroviral Therapy (ART) site facility in Tigray, Ethiopia. Sociodemographic data and associated risk factors were collected using a structured questionnaire. Dried Blood Spot (DBS) samples were collected from each infant and transported by post to Tigray Health Research Institute to detect HIV infection using real-time Polymerase Chain Reaction (PCR). Data were entered into EPI Info version 7, exported and analyzed using Statistical Package for Social Sciences (SPSS) version 22. p-value less than 0.05 was deemed to be statistically significant by Fisher's exact test. Results Three hundred forty infants (175 males, 165 females) met the criteria for selection during the completion of the study and the overall HIV prevalence was found to be 2.1% (n = 7). The majority of infants were from urban areas (n = 246, 72.4%). 45.5% (5/11, p = 0.001) infants were without ARV prophylaxis, 60% (3/5, p = 0.001) infants born to mothers who did not take maternal PMTCT intervention, 43% (3/7, p = 0.001) infants born to mothers who were not enrolled to ART care, and 6.1% (4/66, p = 0.029) infants of unmarried mothers showed statistically significant difference. Conclusions The overall prevalence of HIV among exposed infants was high but lower than the Millennium Development Goal targets. In order to eliminate the mother to child HIV transmission (MTCT) ARV prophylaxis in infants must be strengthened, and enrollment of HIV positive pregnant women to PMTCT and ART care and treatment is needed.